Preliminary ground risk tiering for small unmanned aerial vehicles (sUAV) in metropolitan environments - Sivakumar, Anush Kumar (2022)
Unmanned aircraft systems (UAS) are anticipated to increase in the future and be employed for a variety of applications such as parcel delivery, structural inspections, aerial photography, and surveillance. However, the growth of the UAS industry is impeded by delayed operational approvals and risk assessments. This is likely due to the limited knowledge on the third-party risk (TPR) of UAS operation in the environment. For metropolitan environments like Singapore, the operation of UAS pose high risk to the population on ground due to high population density. Hence, it is of vital importance to assess the ground risk of UAS operations and to subsequently demarcate low, medium, and high areas within the city. In our preliminary study, a ground risk framework, adapted from Joint Authorities for Rulemaking of Unmanned Systems (JARUS) Specific Operations Risk Assessment (SORA), and a semi-quantitative ground risk matrix was established to quantitatively generate UAS failure rate thresholds as well as perform ground risk-tiering of neighborhoods. Ground risk mapping was illustrated for UAS of four different maximum take-off weight (MTOW). It was observed that larger UAS had increased ground risk especially in areas with highly dense population. Study of ground risk in urbanized environments will provide insights on the level of safety required for UAS operations. This could aid aviation authorities in formulating comprehensive risk assessments and reduce the time required to approve UAS operations in metropolitan environments. However, it is noteworthy that further studies are required to validate the results of the risk matrix.